(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: To assess the status of breastfeeding in the first days after birth and to identify several factors related to breastfeeding practices of mothers after giving birth. Subject and method: A cross-sectional descriptive study on 310 postpartum mothers at the Department of Obstetrics and Gynecology - Hue University of Medicine and Pharmacy Hospital from July 2022 to June 2023. Results: 83.2% of mothers are in the age group of 18-35 years old, 50% of mothers have a normal delivery, 35.8 % of mothers breastfeed their babies early, within the first hour after birth, 28.1% of mothers who exclusively breastfeed their babies in the first days after birth, the main reason why mothers do not exclusively breastfeed their babies in the first days after birth is insufficient breast milk 82.1%, 3.9% of mothers expressed colostrum, 70% mothers plan to breastfeed their babies in the first 6 months exclusively. Factors related to early breastfeeding practices are the type of delivery (OR=52.1), the support of health workers in early breastfeeding after birth (OR=4.6), number of births (OR=1,7) with p<0.05. Conclusion: The percentage of mothers who breastfeed their babies early, within the first hour after birth and exclusively breastfeed their babies in the first days after birth is still low; Birth patterns and postpartum support of health workers are related to mothers’ early breastfeeding practices.